2001
DOI: 10.2746/042516401776254907
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis of lung and kidney in Thoroughbreds and ponies

Abstract: Summary Equine lung and kidney organogenesis has not previously been examined with the use of unbiased stereological techniques. The present study examined healthy (control) pony and Thoroughbred lungs and kidneys to establish baseline data of organ development from before birth until maturity at age 3–18 years. Whole left lungs and kidneys were collected from 45 equine postmortem examinations (34 Thoroughbred, 11 pony). Stereological techniques were used to estimate whole kidney, cortex and medulla volume, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
11
1
1
Order By: Relevance
“…Similar studies are beginning to emerge in horses examining the stereological development of various organ systems, including the placenta (Allen et al 2002). One study, reported by Beech et al (2001), has shown that the lungs of ponies are more developed at birth compared with Thoroughbreds; and that lung development in Thoroughbreds continues after birth, a unique micromorphogenic postnatal development in this species compared to others studied. In another study, have shown that the microstructural development of kidneys is equivalent in ponies and Thoroughbreds at birth.…”
Section: Microstructural Studies Of Equine Iugrmentioning
confidence: 73%
“…Similar studies are beginning to emerge in horses examining the stereological development of various organ systems, including the placenta (Allen et al 2002). One study, reported by Beech et al (2001), has shown that the lungs of ponies are more developed at birth compared with Thoroughbreds; and that lung development in Thoroughbreds continues after birth, a unique micromorphogenic postnatal development in this species compared to others studied. In another study, have shown that the microstructural development of kidneys is equivalent in ponies and Thoroughbreds at birth.…”
Section: Microstructural Studies Of Equine Iugrmentioning
confidence: 73%
“…Reports of work performed upon premature and dysmature foals in the 1990s were extended by research devoted to intrauterine growth retardation (IUGR) (Han 1993; Beech et al . 2001).…”
Section: Perinatal Physiology and Medicinementioning
confidence: 99%
“…Diese praenatale Alveolisierung scheint aber nicht gleichmäßig zu erfolgen, sondern unterliegt offenbar bestimmten, vor allem individuellen Einflüssen. So wiesen Beech et al (2001) nach, dass die fetale Lungenentwicklung bei Pony's kompakter und progressiver verläuft als bei Vollblutpferden. Neben der praenatal noch nicht vollendeten Lungenorganogenese spielt wahrscheinlich auch die ungenügende Surfactant-Bildung eine Rolle.…”
Section: Diskussionunclassified